Optimal Blood Pressure Keeps Our Brains Younger - Cherbuin, Nicolas; Walsh, Erin I.; Shaw, Marnie; Luders, Eileen; Anstey, Kaarin J.; Sachdev, Perminder S.; Abhayaratna, Walter P.; Gaser, Christian (Frontiers in Aging Neuroscience, 2021)
Background: Elevated blood pressure is a major health risk factor and the leading global cause for premature death. Hypertension is also a risk factor for cognitive decline and dementia. However, when elevated blood pressure starts impacting cerebral health is less clear. We addressed this gap by estimating how a validated measure of brain health relates to changes in BP over a period of 12 years. Methods: Middle-age (44-46 years at baseline, n=335, 52% female) and older-age (60-64 years, n=351, 46% female) cognitively intact individuals underwent up to 4 brain scans. Brain health was assessed using a machine learning approach to produce an estimate of “observed” age (BrainAGE), which can be contrasted with chronological age. Longitudinal associations between blood pressures and BrainAGE were assessed with linear mixed effects models. Results: A progressive increase in BP was observed over the follow up (MAP = 0.8mmHg/year, SD = 0.92; SBP = 1.41mmHg/year, SD = 1.49; DBP = 0.61mmHg/year, SD = 0.78). In fully adjusted models, every additional 10mmHg increase in blood pressure (above 90 for mean, 114 for systolic, and 74 for diastolic blood pressure) was associated with a higher BrainAGE by 65.7 days for mean, and 51.1 days for systolic/diastolic blood pressure. These effects occurred across the blood pressure range and were not exclusively driven by hypertension. Conclusion: Increasing blood pressure is associated with poorer brain health. Compared to a person becoming hypertensive, somebody with an ideal BP is predicted to have a brain that appears more than 6 months younger at midlife.